(untitled) (Journal of Comparative Social Work, 2024)
There is international interest in approaches to social work focussing on human development and service users’ real freedoms to act. One such example, established in social work, is the capabilities approach. This paper introduces a related, but internationally less well-known concept from German-language philosophy of education discourses, Bildung. It argues that Bildung represents a valuable additional framework for understanding social work in terms of human growth and human flourishing. The concept of Bildung has taken many forms. The term’s changing notions are sketched, starting from its late enlightenment-period origins. Two particular variants are highlighted: the original 18th-century Bildung, which focussed on helping the individual reach a state of agency and Mündigkeit (maturity), a late 20th-century critical theory-influenced Bildung, which focussed on the relationship between the growth of the individual and the society of which they are part. A brief consideration of the capabilities approach provides a context for this discussion of Bildung, with parallels to the capabilities approach noted in the course of outlining Bildung theories. It is suggested that due to their shared tenets, both variants of Bildung can be seen a single concept, one with a strong conceptual closeness to the capabilities approach. When applied to social work, Bildung suggests a shift away from thinking about the person in terms of utilities and outcomes, towards instead an understanding of a person’s humanness in their freedom to choose their own path and become the author of their own life. To conclude, consequences for a Bildung-informed social work are considered. Four are highlighted: the role of the social worker stimulating the service user’s dispositions in the context of their social environment; shifting to a relationship-oriented practice, centring on direct work; utilizing community settings in practice and the importance of refraining from using guidance, persuasion and coercion.